PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK DENGAN VARIABEL KONTROL FREE CASH FLOW (Studi Empiris Pada Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2015) - B2092151011, TJHANG KIAN ON (MAKSI UNTAN, 2017)
This research aims to analyze the effects of independent commissioners, managerial ownership, institutional ownership, the size of the board of directors and audit committee on tax management with free cash flow as a control variable in the consumer goods companies listed on the IDX in period of 2011-2015. The research is an explanatory study using quantitative research method The population were consumer goods companies listed in the Indonesia Stock Exchange in the period 2011-2015. Sampling was conducted through purposive sampling to obtain as many as 25 consumer goods companies listed on Indonesia Stock Exchange in the period 2011-2015 . This research uses secondary data obtained from the financial statements indirectly. The data collected were then processed with SPSS program version 20 which aims to analyze the effects of independent commissioners, managerial ownership, institutional ownership, the size of the board of directors, audit committee and free cash flow on tax management. The results showed that the independent commissioners had a significant positive effects on tax management, and the size of the board of directors had a significant negative effects on Tax Management in consumer goods companies listed on the Indonesia Stock Exchange in period of 2011-2015 , while managerial ownership, institutional ownership, audit committee and free cash flow had an insignificant positive effects on tax management. Free cash flow as a control variable had no effects on Tax Management. Keywords:       Independent Commissioners, Managerial ownership, Institutional Ownership, The size of the Board of Directors and Audit Committee, Tax Management,Free Cash Flow.